Is Adherence to the Healthy Eating Index – 2015 Associated with Rate of Decline in Lung Function. (14th June 2022) - Vonderschmidt, Alexander; Bass, Kathryn; Patchen, Bonnie; Arnold, Kathryn; Shiroma, Eric; Simonsick, Eleanor; Handock, Dana; Cassano, Patricia
Abstract: Objectives: We investigated the hypothesis that a healthier dietary pattern score is associated with higher lung function with stronger associations in smokers. Methods: We studied participants in the Health, Aging, and Body Composition study (n = 2, 549) and the Respiratory Ancillary Study (n = 2, 866). Three dietary pattern scores, based on Healthy Eating Index 2015 (HEI-2015), Alternate Mediterranean Diet (AMED), and Dietary Approaches to Stop Hypertension (DASH), were calculated from FFQs. Associations between the 3 diet pattern scores and lung function [forced expiratory volume in the first second (FEV1 ), forced vital capacity (FVC), and FEV1 /FVC] were estimated using linear mixed effects regression models. Stratified analyses were explored in never vs. ever smokers. Models were run within cohort and meta-analyzed results are presented. Results: The cross-sectional association of dietary pattern and lung function was estimated and a 1-point higher HEI-2015, AMED, and DASH score was associated with a 2 mL, 6 mL, and 6 mL, respectively, higher FEV1 (P < 0.05) at any point in the follow-up. Among ever smokers, the associations were stronger with effect sizes of 6 mL (P = 0.002), 25 mL (P < 0.001), and 7 mL (P < 0.001), respectively. There was little to no association of dietary pattern score and the longitudinal rate of decline in lung function. The findings for FVC were similar, with evidence of cross-sectional but not longitudinal associations. There was little to no association of dietary pattern with FEV1 /FVC. Conclusions: We found a positive cross-sectional association of dietary pattern score with lung function, but little to no association of dietary pattern with longitudinal decline in lung function. The cross-sectional associations were modified by smoking status such that a healthier dietary pattern had a stronger positive association with lung function in cigarette smokers. Funding Sources: This research was supported by R01 HL149352 (PIs: PAC and DBH).